If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 13 = 6x + 113 Reorder the terms: 13 + 10x = 6x + 113 Reorder the terms: 13 + 10x = 113 + 6x Solving 13 + 10x = 113 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 13 + 10x + -6x = 113 + 6x + -6x Combine like terms: 10x + -6x = 4x 13 + 4x = 113 + 6x + -6x Combine like terms: 6x + -6x = 0 13 + 4x = 113 + 0 13 + 4x = 113 Add '-13' to each side of the equation. 13 + -13 + 4x = 113 + -13 Combine like terms: 13 + -13 = 0 0 + 4x = 113 + -13 4x = 113 + -13 Combine like terms: 113 + -13 = 100 4x = 100 Divide each side by '4'. x = 25 Simplifying x = 25
| 66-3x=15x+22 | | x*x+3=28 | | 97-3x=33x+17 | | 18P-0= | | 134-10x=9x+18 | | 4x=36+3x | | -66.66y=22 | | 22=15x | | 25-5= | | -0.003x^2+0.577x+2=0 | | 67x-45y=56x+8y | | 6x^2-19x=14 | | 219-5x=31x+19 | | m^2-10m+18=0 | | 9+-8x=32+-15x | | 11x-19=6x+11 | | 2-(6-2x)=0 | | 12x-15y=80 | | 2x^4-9*x^3-4x^2-5x=0 | | x*3+x^2-8*x-8=0 | | 7y-5=3x+23 | | 4(x+1)-3(x-3)=25 | | -7x+3x^2+2=0 | | (x+4)2=81 | | 137=x+y | | 10x+12=112 | | -3x^2-2x+4=0 | | 4x+62=9x-13 | | 30-6x=3x+18 | | 10-6x=3x+18 | | =4x+15 | | -35-3x=9x+19 |